(untitled) (Nexo Revista Científica, 2021)
Modern transnational companies are increasingly resorting to the open innovation model. The role of innovation is growing all over the world. The development and implementation of innovations in the current activities of companies characterize the effective competitive development of an organization in the market. This model has a number of advantages: faster development of innovations, the ability to save on R&D via outsourcing innovations, access to the most modern innovations of other companies, etc. The purpose of this study is to identify the factors that determine the transition of an increasing number of companies in the world to the open innovation model. In this paper, using the analysis of academic literature, various views on this process have been considered. The work identifies the factors of the development of the open innovation model in the modern world. As a result of the study, the authors have identified the factors that determine the transition of companies to the open innovation model from the traditional closed innovation model.